Obtaining Business Process from Value Process in Blended Value Based Sustainable e-Business Modelling - Dewan, Mohammed Naim Ahmed; Chowdhury Md. Maruf Hossan; Quaddus, Mohammed (ICCIT, 2012)
E-business modelling is already an established term as it converts technology into economic value. Sustainability is another global contemporary issue. While modelling e-business for sustainability it is essential to know the `blended value process' of the proposed value based on which `business process' is derived. The ability to incorporate between the blended value process and the business process is one of the imperative factors that play very significant roles for the companies to be competitive in today's exigent market. A number of research works exist on sustainability, e-business modelling, and value creation but none of them clearly explains the importance of incorporation between these two processes or how business process can be obtained from value process in e-business modelling. We, therefore, demonstrate in this article the process of how business process can be derived from blended value process in sustainable e-business modelling using process algebra. We also provide an illustrative example of our approach for enhanced understanding.